Predictive and Explanatory Relationship Model between Procrastination, Motivation, Anxiety and Academic Achievement - Akpur, Ugur (ANI YAYINCILIK, 2017)
Purpose: The purpose of this study is to determine the predictive and explanatory relationship model between procrastination, motivation, anxiety and academic achievement of university students. Research Methods: In this study, a causal research design was used. The study group consisted of 211 participants. In order to determine their motivation levels, Academic Motivation Scale (AMS); their anxiety levels, Foreign Language Classroom Anxiety Scale (FLCAS) and their procrastination levels, Aitken Procrastination Inventory (API) were all applied. Students' grades during the term were considered as the criteria for academic achievement. Data were obtained through Structural Equation Model (SEM). Findings: Within the theoretical background, the proposed model was tested, and after path analysis it was modified and verified by testing through fitness indexes. The values confirmed that the model is compatible and the goodness-of-fitness values are within the limits. Findings reveal that, there is not a significant relationship between anxiety and academic achievement. However, both the relationship between academic procrastination and academic achievement and the relationship between motivation and academic achievement are significant. According to findings, the relationship between academic procrastination and motivation is significant and negative. Considering the findings, the predictive and explanatory relationship pattern between procrastination, motivation anxiety and academic achievement was suggested as a model. Implications for Research and Practice: Procrastination and motivation are significant variables in predicting academic achievement. Future studies could focus on other affective variables that are thought to have relationship to academic achievement. (C) 2017 Ani Publishing Ltd. All rights reserved
Keywords: affective factors; language learning; structural equation modelling; LANGUAGE ANXIETY; SELF-EFFICACY; STUDENTS; ATTITUDES; Education & Educational Research